2022
DOI: 10.1111/hsc.13966
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers to postpartum depression and anxiety screening: A qualitative study of Victorian maternal and child health nurses' practices

Abstract: In Victoria, Australia, Maternal and Child Health nurses (MCHNs) play a key role in facilitating the timely identification of Postnatal Depression and Anxiety (PNDA). Understanding MCHNs' screening practices, and the factors which impact them, is central to ensuring that future screening policy agendas are evidence‐based and able to support MCHNs in carrying out this critical work. Yet, little is known about this subject. The purpose of this study was to gain an in‐depth understanding of MCHNs' screening pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…Qualitative studies conducted on Perinatal depression screening practice in Amhara Regional State, Ethiopia, share common barriers with our study findings: health administrators' low literacy, community awareness, and organizational challenges (38). A qualitative descriptive study done in Victoria, Australia indicated language barrier between professionals and patients also factor influencing screening practice (39).…”
Section: Discussionsupporting
confidence: 72%
“…Qualitative studies conducted on Perinatal depression screening practice in Amhara Regional State, Ethiopia, share common barriers with our study findings: health administrators' low literacy, community awareness, and organizational challenges (38). A qualitative descriptive study done in Victoria, Australia indicated language barrier between professionals and patients also factor influencing screening practice (39).…”
Section: Discussionsupporting
confidence: 72%